Age-realted dementia in Kazahstan: adaptation of the 10/66 dementia research group population -based study protocol - Kaiyrlykyzy, A.; Adambekov, Sh.; Alimbetov, D.; Askarova, Sholpan (Nazarbayev University, 2014)
Background. The prevalence of dementia is increasing worldwide as the population ages and affects 10 % of the population over 65 years old and 40 % of people over the age of 80.[1] In Kazakhstan, as well as in other countries around the world, the population of aged people has been increasing over the past decades. According to available statistics, by the end of 2013, the percentage of people aged 65 and older in Kazakhstan was 6.7% [2]. Given the fact that Kazakhstan's current population is about 17,221 million people [2], and based on data from the global statistics, it can be assumed that at least 115,000 elderly people could be suffering from age-related dementia. Nevertheless, such pathology is currently may not being diagnosed in Kazakhstan; consequently giving no accurate statistical data on the number of people suffering from this age-related pathology. Thus, the aim of this study is to estimate true prevalence of dementia and assess the risk factors associated with the disease.
Keywords: dementia diagnosis; subtypes; mental disorders; physical health; anthropometry; demographics; care arrangements